PENGARUH DUKUNGAN SOSIAL SUAMI TERHADAP KONFLIK PERAN GANDA WANITA KARIR (LPPM Universitas HKBP Nommensen, 2024)
This study aims to determine the effect of husband's social support on dual role conflict in career women. The hypothesis put forward in this study is that there is an influence between husband's social support and dual role conflict in career women. The population in this study are career women who have a dual role, namely those who work and also become housewives in the city of Medan. The sample in this study were 350 career women who were selected by non-random sampling using purposive sampling technique. The data collection tool used in this study is a scale from the husband's social support aspect by Sarafino (2014) and a scale from the Dual Role Conflict aspect by Sekaran. The data analysis used in this study is the Simple Linear Regression Correlation Test. The results showed that there was an influence between husband's social support and dual role conflict in career women with (r = 0.517) and (p = 0.000) (p> 0.05). This shows that there is a negative relationship, namely the more positive the husband's social support, the more negative the dual role conflict and vice versa, the more negative the husband's social support, the more positive the dual role conflict.